Dominant Power and Its Bandwagoning Effect on Justice in the Middle East - Radiatie, Novalita; Iskandar, Winda Nurlaily Rafikalia; Dasadwiastaning, Valentia Nadya; Morley, Peter John (Perhimpunan Intelektual Muslim Indonesia, 2025)
This research contributes to complementing the study of realism in international relations through bandwagoning by analyzing interdependence in the alliance of Muslim countries in the Middle East. The United States, as a dominant power, always takes part in the political map in the Middle East, which is considered strategic, by offering political, military, and economic assistance. The response of countries in the Middle East varies, depending on their national agendas and diplomatic relations. In the Israeli-Palestinian conflict, several Muslim countries in the Middle East lost the value of impartial justice and depended on the interests of allies with the United States. The principle of independent justice has become blurred, leading to bias in the actions of Muslim countries that tend to support the United States. This research uses the concept of bandwagoning popularized by Kenneth Waltz in Theory of International Politics. This alliance contributes to the value of justice to follow the dominant power rather than uphold justice in the Israeli-Palestinian conflict. The method used in this research is qualitative, with a descriptive approach based on secondary data collection. The analysis in this research compares several specific phenomena in the Middle East region, focusing on Muslim countries, including Saudi Arabia, Egypt, Qatar, and Bahrain. This study uses national interest mapping to show that the interdependence of Muslim countries choosing to ally with the United States influences political actions and decisions without regard to the principle of impartial justice.